Interferon-γ signaling in human iPSC–derived neurons recapitulates neurodevelopmental disorder phenotypes - Warre-Cornish, Katherine; Perfect, Leo; Nagy, Roland; Duarte, Rodrigo R. R.; Reid, Matthew J.; Raval, Pooja; Mueller, Annett; Evans, Amanda L.; Couch, Amalie; Ghevaert, Cedric; Mcalonan, Grainne; Loth, Eva; et al. (Science Advances, 2020)
Maternal immune activation increases the risk of neurodevelopmental disorders. Elevated cytokines, such as interferon-γ (IFN-γ), in offspring’s brains play a central role. IFN-γ activates an antiviral cellular state, limiting viral entry and replication. Moreover, IFN-γ is implicated in brain development. We tested the hypothesis that IFN-γ signaling contributes to molecular and cellular phenotypes associated with neurodevelopmental disorders. Transient IFN-γ treatment of neural progenitors derived from human induced pluripotent stem cells increased neurite outgrowth. RNA sequencing analysis revealed that major histocompatibility complex class I (MHCI) genes were persistently up-regulated through neuronal differentiation—an effect that was mediated by IFN-γ-induced promyelocytic leukemia protein (PML) nuclear bodies. Critically, IFN-γ-induced neurite outgrowth required both PML and MHCI. We also found evidence that IFN-γ disproportionately altered the expression of genes associated with schizophrenia and autism, suggesting convergence between genetic and environmental risk factors. Together, these data implicate IFN-γ signaling in neurodevelopmental disorder etiology.
CRIS-Team Scopus Importer:2023-03-27